Rewind, Play, Fast Forward: The Past, Present and Future of the Music Video - Wübbena, Thorsten; Keazor, Henry (transcript, 2015)
Due to shifts in the contexts of the production and presentation of the music video, more and more people start to talk about a possible end of this genre. At the same time disciplines such as visual-, film- and media-studies, art- and music-history begin to realize that despite the fact that the music video obviously has come of age, they still lack a well defined and matching methodical approach for analyzing and discussing videoclips.For the first time this volume brings together different disciplines as well as journalists, museum curators and gallery owners in order to take a discussion of the past and present of the music video as an opportunity to reflect upon suited methodological approaches to this genre and to allow a glimpse into its future.